2020
DOI: 10.3847/1538-4357/abc342
|View full text |Cite
|
Sign up to set email alerts
|

NuSTAR Survey of Obscured Swift/BAT-selected Active Galactic Nuclei. II. Median High-energy Cutoff in Seyfert II Hard X-Ray Spectra

Abstract: Broadband X-ray spectroscopy of the X-ray emission produced in the coronae of active galactic nuclei (AGNs) can provide important insights into the physical conditions very close to their central supermassive black holes. The temperature of the Comptonizing plasma that forms the corona is manifested through a high-energy cutoff that has been difficult to directly constrain even in the brightest AGN because it requires high-quality data at energies above 10 keV. In this paper we present a large collection of co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 102 publications
4
59
1
Order By: Relevance
“…Moreover, compared with previous fits of a single power-law plus a xillver component, Model A describes the iron complex region with a neutral distant reflection model, although we still can see some systematic residuals in the upper left panel of Figure 5 around the Fe K energies. However, the most peculiar aspect of the warm corona model is the relatively low temperature of the hot corona, which is uncommon for AGN (e.g., Nandra & Pounds 1994;Ricci et al 2017;Baloković et al 2020). This is further discussed in Section 4.1.…”
Section: Model A: Warm Coronamentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, compared with previous fits of a single power-law plus a xillver component, Model A describes the iron complex region with a neutral distant reflection model, although we still can see some systematic residuals in the upper left panel of Figure 5 around the Fe K energies. However, the most peculiar aspect of the warm corona model is the relatively low temperature of the hot corona, which is uncommon for AGN (e.g., Nandra & Pounds 1994;Ricci et al 2017;Baloković et al 2020). This is further discussed in Section 4.1.…”
Section: Model A: Warm Coronamentioning
confidence: 98%
“…Another 18 keV). Though it is uncommon for most of studied AGNs (e.g., Fabian et al 2015Fabian et al , 2017Marinucci et al 2016;Baloković et al 2020), NuSTAR has reported several lowtemperature coronae in recent years, e.g., ∼25 keV (MCG-05-23-016, Baloković et al 2015), ∼50 keV (Ursini et al 2015), ∼15 keV (Ark 564, Kara et al 2017), ∼12 keV (GRS 1734-292, Tortosa et al 2017), and ∼40 keV (IRAS 00521-7054, Walton et al 2019). Ricci et al (2018) also reported a large number of sources with temperatures below 50 keV and found a statistical dependence of the cutoff energy on the Eddington ratio.…”
Section: Physical Properties Of the Warm Corona Modelmentioning
confidence: 99%
“…The value of the cut-off energy has been chosen to be consistent with previous similar works (see e.g., Marchesi et al 2017b;Zhao et al 2019b,a). Moreover, recent works (e.g., Baloković et al 2020) show that it is a reasonable value for the extension of the continuum.…”
Section: Tablementioning
confidence: 91%
“…We fit this component using a redshifted power law component with a high-energy cut-off zcutoffpl (xspec model). Here the cut-off energy is fixed arbitrarily to 300 keV (Baloković et al 2020); however, since we only consider here X-ray emission below ∼10 keV, the chosen energy is irrelevant as soon as it is above a few tens of keV. The free parameters of this component are the photon index (Γ) and the normalization (F), which is defined as the intrinsic flux of the cut-off power law in the 2 to 10 keV band.…”
Section: Primary Emissionmentioning
confidence: 99%